2019
DOI: 10.5267/j.dsl.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of decision support system for e-supplier selection in Indian mechanical manufacturing industry using distance based approximation

Abstract: This paper proposes a framework to develop a deterministic model for the valuation, selection and grading (ranking) of e-suppliers by using Modified Distance Based Approach (MDBA), which has not been used earlier in e-supplier selection. The e-supplier selection system performs a major part for the successful running of any supply chain. Thus, for effective running of any supply chain, it is necessary to build a system for the selection of e-supplier. Building such a decision support system software is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
(134 reference statements)
1
3
0
Order By: Relevance
“…For the choice of alternatives, if alternatives like Alts1, Alts2, Alts3, Alts7, and Alts8 are removed from the set, it can be concluded that fuzzy DEMATEL-DBA provides better results with less time and easier procedure when compared with fuzzy DEMATEL-TOPSIS. This conclusion is consistent with that concluded by Jain et al (2016), Rishi Kumar & Garg (2010), and A Kumar et al (2019) (Jain et al, 2016;Rishi Kumar & Garg, 2010;A Kumar et al, 2019). Similarly, if only Alts3, Alts4, and Alts10 are considered, fuzzy DEMATEL-DBA also gives a faster solution than DEMATEL-GRA.…”
Section: Fig 6: Rank Comparison Between Fuzzy Dematel and Dematelsupporting
confidence: 89%
See 3 more Smart Citations
“…For the choice of alternatives, if alternatives like Alts1, Alts2, Alts3, Alts7, and Alts8 are removed from the set, it can be concluded that fuzzy DEMATEL-DBA provides better results with less time and easier procedure when compared with fuzzy DEMATEL-TOPSIS. This conclusion is consistent with that concluded by Jain et al (2016), Rishi Kumar & Garg (2010), and A Kumar et al (2019) (Jain et al, 2016;Rishi Kumar & Garg, 2010;A Kumar et al, 2019). Similarly, if only Alts3, Alts4, and Alts10 are considered, fuzzy DEMATEL-DBA also gives a faster solution than DEMATEL-GRA.…”
Section: Fig 6: Rank Comparison Between Fuzzy Dematel and Dematelsupporting
confidence: 89%
“…This approach mainly considers the distance between the alternatives and optimal points. Therefore, the determination of the optimal point and the ideal solutions are prioritized (Rishi Kumar & Garg, 2010;A Kumar et al, 2019). According to Gupta et al (2018), i i1 i2 ij A = (a , a , ..., a ) is a set of alternatives and op1 op2 opj OP = (a , a , ..., a ) represents a set of optimal points that are the best values of criteria used to rank alternatives in multi-dimensional space (Aakash Gupta et al, 2018).…”
Section: Distance Based Approximation Methods (Dba) With a Considerat...mentioning
confidence: 99%
See 2 more Smart Citations